Answers

  • Brainly User
2015-08-18T11:33:59+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
CotA=1/tanA
tanA=1/cotA
tanA/1-cotA+cotA/1-tanA=1+secAcosecA
tanA/1-1/tanA + cotA/1-1/cotA
tanA/tanA-1/tanA + cotA/cotA-1/cotA
tanA²/tanA-1+1/tanA/1-1/tanA
tanA²/tanA-1 - 1/tanA(tanA-1)
taking lcm on both sides
tanA³-1/tanA(tanA-1)
using identity a³+b³ =(a-b)(a²+ab+b²)
(tanA-1)(tan²A+tanA+1)/tanA(tanA-1)
(tan²A +tanA+ 1)/tanA
tan²A/tanA+tanA/tanA+1/tanA
tanA+1+cot A
tanA=sinA/cos A and cosA/sinA=cotA
sinA/cosA+1+cosA/sinA
(sin²A+cos²A+cosAsinA)/cosAsinA
sin²A+cos²A=1
1/cosAsinA + 1
1/cosA=secA and 1/sinA=cosecA 
secAcosecA+1 
hence lhs = rhs so proves 
0